Praktik Ekonomi Lokal Masyarakat Melalui Bisnis Mangga dalam Perspektif Fikih Muamalah - Muhammad Nasrudin fh; Muhammad Fahmul Iltiham; Muhammad Nizar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine community economic empowerment through the mango business from the perspective of muamalah fiqh in Oro-Oro Ombo Kulon Village, Rembang District, Pasuruan Regency. Using a descriptive qualitative approach, this research identifies the economic potential of the mango business in the village and analyzes the application of muamalah fiqh principles in every aspect of the business. The research results show that Oro-Oro Ombo Kulon Village has great potential in mango cultivation and economic empowerment through this business has had a positive impact on the local community. The application of the principles of muamalah fiqh, such as justice, transparency and honesty, in the mango business also creates an ethical and sustainable business environment. This research provides recommendations for infrastructure development, training, product diversification, collaboration, and marketing strategies that can increase the effectiveness of economic empowerment through the mango business and create a business model that is in accordance with Islamic principles.